Особливості догляду за шкірою хворих на розацеа у різні періоди перебігу захворювання - Василенко, Анна Василівна; Василенко, А. В.; Vasylenko, A. V. (My University, 2018)
Мета роботи – встановити та обґрунтувати сучасний метод запобігання виникнення рецидивів розацеа, дати оцінку його ефективності. Представлено сучасні данні, присвячені комплексному вивченню клінічних особливостей різних клінічних форм та періодів розацеа і розробці сучасних методів догляду за шкірою у міжрецидивний період для якісної пролонгації ремісії. Досліджено 80 хворих на розацеа, серед них було 54 жінки (67,5%) та 26 чоловіків (32,5%). Серед досліджуваних – 20 пацієнтів із вперше виявленою розацеа та 60 пацієнтів із рецидивами розацеа. Контрольну групу складали 20 осіб практично здорових пацієнтів. Протягом лікування оцінювали клінічні прояви захворювання, за бальними шкалами визначали індекс DLQI. Виявлені зміни свідчать, що рецидиви розацеа протікають більш злоякісно, мають більш тяжкий перебіг та свої особливості. Данні проведеного дослідження свідчать про важливість раннього виявлення патогенетичних та клінічних змін, для коректного підбору комплексної диференційованої терапії у гострий період та спеціальних косметичних засобів для шкіри у періоди ремісії, для запобігання розвитку рецидивів захворювання. Представлены современные данные, посвященные комплексному изучению клинических особенностей различных клинических форм и периодов розацеа и разработке современных методов ухода за кожей в межрецидивный период для качественной пролонгации ремиссии заболевания. Исследовано 80 больных розацеа, среди них было 54 женщины (67,5%) и 26 мужчин (32,5%). Среди исследуемых – 20 пациентов с впервые выявленной розацеа и 60 пациентов с рецидивами розацеа. Контрольную группу составили 20 человек практически здоровых пациентов. Во время лечения оценивали клинические проявления заболевания по балльной шкале определяли индекс DLQI. Выявленные изменения свидетельствуют, что рецидивы розацеа проходят более злокачественно, имеют более тяжелое течение и свои особенности. Данные проведенного исследования свидетельствуют о важности раннего выявления патогенетических и клинических изменений, для корректного подбора комплексной дифференцированной терапии в острый период и специальных косметических средств для кожи в периоды ремиссии, для предотвращения развития рецидивов заболевания. According to the literature of recent years, it is known that rosacea is a topical medical and social problem due to the widespread morbidity and frequent recurrence of the disease. There remain unresolved questions regarding aetiology, some aspects of pathogenesis, treatment of this dermatosis and, especially, preventive measures. There is no research on the features of the clinic and the course of recurrence of rosacea. The article presents modern data on the complex study of the clinical features of various clinical forms and periods of rosacea and the development of modern skin care methods in the interdivision period for qualitative prolongation of remission. Material and methods. 80 patients with rosacea were studied. There were 54 women (67.5%) and 26 men (32.5%) among them. Moreover, 20 patients were with the first identified rosacea and 60 patients with relapses of rosacea. The control group consisted of 20 persons of practically healthy patients. Results and discussion. During the treatment, the clinical manifestations of the disease were assessed, and the DLQI index was determined on the ball scales. In a comparative analysis of data on anamnesis and clinical manifestations, it was found out that certain features were identified in patients with recurrent rosacea. Thus, in 5 out of 20 patients (25%) with the newly discovered rosacea and in 52 of 60 patients (86.6%) with recurrent rosacea, there were subjective complaints (itching, burning and tingling, stinging, dry skin with peeling, feeling tides to the face, swelling of the face, feeling of crawling ants, and numbness), which, in turn, caused more significant psycho-emotional disorders. Patients with rosacea, who were examined both in the primary, and in the comparison groups, taking into account the generally accepted recommendations, received a standard therapy in the period of exacerbation of the disease. We have developed a scientifically based method for the comprehensive treatment of patients with relapses of rosacea in the acute period. The features of this method are the additional use of drugs that affect most pathogenesis factors and aimed at eliminating all identified pathogenetic disorders and in the complex have a stronger effect on the stabilization of the whole organism as a whole. In order to prevent the development of recurrences of rosacea, it was also recommended to use special medical care products for care. Thus, patients after the course of basic therapy passed to special medical care for sensitive, prone to reddening of the skin. The revealed changes indicated that recurrences of rosacea proceed more malignant, have a more severe course and their peculiarities. The data of the study showed the importance of early detection of pathogenic and clinical changes to correct a comprehensive selection of differentiated treatment in the acute phase and special cosmetics for skin in remission to prevent relapse of the disease. Conclusions. The results of comparison of the further course and clinical manifestations of dermatosis after the treatment showed the benefit of the effectiveness of the proposed method of complex therapy and prevention of the development of relapses in patients with rosacea. Rational treatment with the subsequent appointment of prophylactic cosmetic skin care is a key factor in preventing the development of relapses of rosacea and confirms the validity and effectiveness of our treatment method, prevention and prediction of relapse.
Особенности ухода за кожей больных розацеа в разные периоды течения заболевания
Features of skin care for patients with rosacea in different periods of the disease
Keywords: розацеа; рецидиви; патогенез; догляд за шкірою; якість життя; рецидивы; уход за кожей; качество жизни; rosacea; relapses; pathogenesis; skin care; quality of life